2004
DOI: 10.1093/jhered/esh067
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microsatellites and Parentage Testing in Saltwater Crocodiles

Abstract: Fifteen microsatellite loci were evaluated in farmed saltwater crocodiles for use in parentage testing. One marker (C391) could not be amplied. For the remaining 14, the number of alleles per locus ranged from two to 16, and the observed heterozygosities ranged from 0.219 to 0.875. The cumulative exclusion probability for all 14 loci was .9988. the 11 loci that showed the greatest level of polymorphism were used for parentage testing, with an exclusion probability of .9980. With these 11 markers on 107 juvenil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 4 publications
5
47
0
3
Order By: Relevance
“…Here, we used the same microsatellite loci to compare the genetic diversity of C. mindorensis to C. acutus, C. niloticus, C. porosus and C. siamensis. The heterozygosity estimates from our data for C. acutus, C. niloticus, C. porosus and C. siamensis fall within the ranges of estimates previously reported for captive purebred C. siamensis, Ho = 0.42±0.17 (FitzSimmons et al 2002), farmed C. porosus, Ho = 0.59 (Isberg et al 2004) and in wild populations of C. niloticus, He = 0.27-0.61 (Hekkala et al 2010) and Ho = 0.51 (Bishop et al 2009), C. moreletti, Ho = 0.49 (Dever et al 2002) and Melanosuchus niger, Ho = 0.47-0.70 (de . We found that genetic diversity measures for C. mindorensis were lower compared to C. acutus, C. niloticus, C. porosus and C. siamensis, whether using traditional F ST and heterozygosity measures or by transforming such measures into diversity indices.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here, we used the same microsatellite loci to compare the genetic diversity of C. mindorensis to C. acutus, C. niloticus, C. porosus and C. siamensis. The heterozygosity estimates from our data for C. acutus, C. niloticus, C. porosus and C. siamensis fall within the ranges of estimates previously reported for captive purebred C. siamensis, Ho = 0.42±0.17 (FitzSimmons et al 2002), farmed C. porosus, Ho = 0.59 (Isberg et al 2004) and in wild populations of C. niloticus, He = 0.27-0.61 (Hekkala et al 2010) and Ho = 0.51 (Bishop et al 2009), C. moreletti, Ho = 0.49 (Dever et al 2002) and Melanosuchus niger, Ho = 0.47-0.70 (de . We found that genetic diversity measures for C. mindorensis were lower compared to C. acutus, C. niloticus, C. porosus and C. siamensis, whether using traditional F ST and heterozygosity measures or by transforming such measures into diversity indices.…”
Section: Discussionsupporting
confidence: 89%
“…Microsatellites have been used to investigate population structure and gene flow in wild populations of Morelet's Crocodile Crocodylus moreletii Duméril & Bibron, 1851 (Dever & Densmore 2001;Dever et al 2002), American Alligator Alligator mississippiensis Daudin, 1802 (Glenn et al 1998;Davis et al 2002) and Black Caiman Melanosuchus niger Spix, 1825. Microsatellites have also been useful in parentage analysis in Saltwater Crocodiles C. porosus Schneider, 1801 (Isberg et al 2004), in determining and maintaining genetic variability in crocodiles bred for the leather trade (Flint et al 2000;FitzSimmons et al 2002) and to build the scaffolding for a genetic linkage map (Miles et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…This principle has been shown by Isberg et al (2004), Lee and Cho (2006) and Rohrer et al (2007). Especially the work of Isberg et al (2004) on saltwater crocodiles is a good example on how complicated the parental identification and/or verification can be in non-commercial conditions. If the problem of erratically assigned parents can be solved for animals kept under natural conditions, e.g.…”
Section: Introductionmentioning
confidence: 91%
“…Other authors have applied microsatellites in parentage testing in Cr. porosus (Isberg et al, 2004) and in analyses of mating patterns in A. mississippiensis (Davis et al, 2001b). Davis et al (2001b) also inferred multiple paternity, ''the occurrence of offspring within a single clutch being fathered by more than one male,'' in seven of 22 clutches of A. mississippiensis.…”
mentioning
confidence: 99%